Dental students’ perception towards internal medicine - Shrestha, Deepak Sundar (Journal of Chitwan Medical College, 2021)
Background: A qualified dental surgeon is expected to be well versed in the essentials of medicine. However, many factors may affect their interest level, which may determine how well they learn to be a competent practitioner. This study aimed at understanding the interest of students towards internal medicine and to explore ways for enhancing their interest. Methods: It was cross-sectional study conducted amongst students from third year, fourth year and internship at People’s Dental College and Hospital after Institutional Review Committee approval. The study took place during February 2021 to March 2021. SPSS version 21 was used to perform Chi square test to see association of different variables. Results: Most students (93.7%) were interested in internal medicine. Cardiovascular and respiratory system were most interesting topics. Total 86.7% students agreed that learnings in medicine will be useful. However, 47.6% and 49.7 % didn’t think that the knowledge and skills they acquire would be enough for them. Most favored combining different teaching learning methods to increase understanding and interaction. Overall, 65% of students felt time allotted for internal medicine was inadequate and 40.2% proposed to include it in third and fourth years. Majority (51%) recommended more emphasis on practical classes and demonstration. Conclusions: Combining different teaching learning methods appealing to the participants should be used to enhance their understanding and to increase interaction. Revision at the end of lecture is necessary. Increased years of teaching with focus on applied knowledge, enhanced clinical exposure and practical placements during internship would be helpful.